Theoretical and experimental study of isothiazolinone adsorption onto ordered mesoporous silica - Mardones, Lucas (2016)
Mesoporous silica SBA-15 particles were synthesized in order to evaluate their effectiveness asencapsulating agents for a commercial biocide composed of a mixture of methylisothiazolinone andchloromethylisothiazolinone (MIT/CMIT). Three powdered samples of silica particles having differenttextural properties, sizes and morphologies were hydrothermally obtained and then characterized bySEM, TEM, SAXS, and nitrogen adsorption–desorption measurements. Adsorption of the biocide on theprepared materials was investigated, and the results showed that adsorption capacities increase as theparticle size becomes smaller. Higher biocide amounts were also retained on particles having increasedpore size and pore volume. Additionally, a most probable interaction mechanism between MIT/CMIT andSBA-15 is proposed on the basis of molecular modeling calculations. The theoretical approach indicatesthat two adsorption geometries with comparable minimum levels of strength can be adopted by the bio-cide: planar adsorption when the biocide molecule rings are adsorbed on the silica surface and verticaladsorption when the O atom of the MIT/CMIT interacts with the H atom of silanols.